COMPARATIVE STUDY OF FUNCTIONAL OUTCOME OF HAMSTRING VERSES BPTB GRAFT IN ACL RECONSTRUCTION - TAREEN, N; AMIN, MS; NAQVI, AN; NADEEM, M; SHOAIB, M; KHAN, B (Biological and Clinical Sciences Research Journal, 2024)
Anterior cruciate ligament (ACL) injuries are among the most common knee injuries requiring surgical intervention. The choice of graft for ACL reconstruction—hamstring or bone-patellar tendon-bone (BPTB)—remains debatable due to differences in functional outcomes and complications. Objective: To compare the functional outcomes of ACL reconstruction using hamstring and BPTB grafts regarding knee stability, range of motion (ROM), patient satisfaction, and complication rates. Methods: This retrospective study included 150 patients who underwent ACL reconstruction, divided into two groups: 75 received hamstring grafts (Group A), and 75 received BPTB grafts (Group B). Clinical evaluations and patient-reported outcomes were assessed at 6 and 12 months post-surgery. Statistical analysis was performed using SPSS software, with a p-value <0.05 considered significant. Results: Knee stability was achieved in 90% of patients in the hamstring group and 94% in the BPTB group. Group A demonstrated better ROM recovery (130° ± 5 vs. 125° ± 5) and a lower complication rate (12% vs. 25%). Patient satisfaction was higher in the hamstring group (92% vs. 85%), while return-to-sport rates were slightly higher in the BPTB group (82% vs. 78%). Anterior knee pain was more prevalent in the BPTB group (28% vs. 10%). Conclusion: Both grafts are effective for ACL reconstruction, but each has distinct advantages and limitations. The BPTB graft offers superior initial stability and return-to-sport rates but is associated with higher complications. The hamstring graft provides better ROM, fewer complications, and higher patient satisfaction, making it a preferred choice for smoother rehabilitation. Graft selection should be individualized based on patient needs and activity levels.